HUBUNGAN ANTARA SIKAP, KEMANDIRIAN, DAN GAYA BELAJAR DENGAN HASIL BELAJAR SISWA KELAS VIII SMP MADANI MAKASSAR - Yusri Suheni; Hasria Alang; Moh. Mulyadi Prasetyo (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2023)
The aim of the research was to determine the relationship between the variables of attitude, independence and learning style and the learning outcomes of class VIII students at Madani Middle School, Makassar. This type of research is ex post facto, namely research carried out on events that have occurred to reveal existing data or describe research variables without providing treatment or manipulation of the object under study. The data collection technique is in the form of a questionnaire which is used to obtain data on students' attitudes, independence and learning styles. Data collection on students' attitudes, learning independence and learning styles was carried out through administering questionnaires, while data on student learning outcomes was obtained from odd semester test scores. Data analysis uses inferential statistics with product moment correlation tests, simple and multiple fiber regression assisted by SPSS 20.0 for Windows software. Based on the research results, it was concluded that: there is a positive relationship between attitudes and the learning outcomes of class VIII students at Madani Middle School, Makassar, with a percent correlation value of 0.385. There is a positive relationship between learning independence and learning outcomes for class VIII students at Madani Middle School, Makassar, with a percent correlation value. of 0.299, there is a positive relationship between learning styles and the learning outcomes of class VIII students at Madani Makassar Middle School, with a percentage correlation value of 0.232 and that there is a positive relationship between attitudes and learning outcomes with a percent correlation value of 0.385, there is a positive relationship between learning independence with learning outcomes with a percent correlation value of 0.299 and there is a positive relationship between learning style and learning outcomes with a percent correlation value of 0.232.